GAYA KEPEMIMPINAN DEMOKRATIS KEPALA MADRASAH DALAM PENINGKATAN KINERJA TENAGA ADMINISTRASI TATA USAHA DI MTS NEGERI 12 INDRAMAYU - Arief Rachman Fauady; Ukhti Fitriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The leadership of the madrasa head will be successful in leading by implementing various types of leadership styles. Among other types of democratic leadership style, a good leader must be able to manage his institution by coaching the performance of administrative staff. Coaching is carried out for the success of the administrative process in an educational institution and to improve administrative performance. Therefore, the aim of this research is to determine the democratic leadership style of madrasa heads through coaching the performance of administrative staff at MTs Negeri 12 Indramayu. The method used in this research is a descriptive qualitative research method. The research subjects were madrasa heads, heads of administration and teachers. This research data collection technique uses observation, interviews and documentation. The results of this research show that the leadership style applied by the head of MTs Negeri 12 Indramayu is a democratic leadership style seen from the way his leadership is open and always deliberative in making decisions. The efforts of the madrasa head in developing the performance of administrative administrative staff by conducting training, creating a conducive work environment, fostering a sense of brotherhood, developing the mindset of educational staff, madrasa work plans (RKM), madrasa development plans (RPM). The results of the madrasah head's democratic leadership style in developing the performance of administrative administrative staff are good. The advantages of the madrasah head's democratic leadership style can be seen from the way the madrasah head responds to problems that occur within the madrasah environment. The drawback is that the decision-making process takes a long time because it is taken by deliberation.